أثر مشكلة المياه على العلاقات الإقتصادية بين العراق وتركيا (المجلة العراقية للعلوم الاقتصادية, 2018)
International relations Established base on interests, benefits and objectives for countries. As is the case for Iraqi - Turkish relations, its punctuated by a lot of events and developments, positive and negative. over the previous times, and among those developments, emergence the water problem between the two countries which took a large portion of those relationships and have resulted in a lot of tensions between the two countries as a result of policies and water projects undertaken and carried out by Turkey on the Euphrates and Tigris rivers, caused a significant damage to Iraq and its agricultural sector which, in particular, adversely affacts on the domestic agricultural product, and other effect agricultural commodities imported by Iraq, including the Turkish one.